Assessment of Detrimental Health Effect of Radiation Associated with Diagnostic X-Ray Examinations at Four Centres in Nigeria (2011)
Radiation exposure during diagnostic X-ray examinations has been widely reported as one of the sources of cancer induction. Information on X-ray machine and exposure parameters are crucial to risk assessment, which in turn are important for optimization of radiation protection measures. The documentation of radiation risk in Nigeria is sparse and hence the effectiveness of radiation protection measures at diagnostic centres has not been well established. This work was aimed at measuring effective dose received by patients during diagnostic x-ray examinations and estimating the associated risk. Between the years 2004 and 2006, the beam output of x-ray machines at four diagnostic centres with adequate regulatory activities were measured with non-invasive x-ray meter. These centres include University College Hospital (UCH) Ibadan, Twotees Diagnostic Centre (TDC) Ibadan, Obafemi Awolowo University Teaching Hospital Complex (OAUTHC) Ile-Ife and National Hospital Abuja (NHA). Field sizes, focus to skin distance (FSD), tube filtration, operating potential (kVp) and tube loading (mAs) were measured and used to calculate Dose Area Product (DAP) per patient. Data on age and examination type were recorded for 1034 patients which include 310(UCH), 276(TDC), 220(OAUTHC) and 228(NHA). These and calculated DAP were used to run Monte Carlo program to obtain effective dose. The risk of cancer was thereafter estimated using fatal cancer risk factor of 5 x 10-2 Sv-1. The results obtained were compared with the risk estimates recommended by the International Commission on Radiological Protection (ICRP). X-ray field sizes and FSD of the examinations considered ranged from 8 cm x 5 cm to 40 cm x 35 cm and 75 cm to 139 cm respectively. The tube filtrations (mmAl) at UCH, TDC, OAUTHC and NHA were 1.7, 2.7, 1.7 and 1.0 +1.0 mmCu respectively while the mean exposure parameters (kVp, mAs) were 69, 45; 76, 79; 100, 83; and 75, 28 respectively. Analysis of examination type showed that thoracic x-ray examination was the most common (74.0%). This was followed by head and neck (11.0%), pelvic (8.0%), lower limb (4.0%), abdomen (2.0%) and upper limb (1.0%). The mean age (years) of patients was 38±1 at UCH, 32±1 at TDC, 27±1 at OAUTHC and 28±1 at NHA. Examination procedures were the same in all centres except the use of anti-scatter grid for thoracic examination at OAUTHC. In all x-ray examinations, DAP (mGycm2) generally ranged from 70 to 38,155. The range of effective doses (mSv) at UCH, TDC, OAUTHC and NHA were 0.01–0.11, 0.01–0.17, 0.24–4.74 and 0.01–0.10 respectively while the corresponding estimated risks of cancer per million were 2–9, 2–22, 100–400 and 2-6. The values at OAUTHC were higher than ICRP risk estimates of 35 cancer cases per million. This was traceable to selection of high kVp with high mAs and insufficient tube filtration. Radiation risks associated with diagnostic X-ray examinations were within acceptable limit except at OAUTHC. For radiation risks to be within the recommended limit, the use of high kVp with low mAs and careful application of anti-scatter grid are encouraged.